DISCOURSE ANALYSIS AND THE COMMUNICATIVE COMPETENCE OF ENGLISH LANGUAGE LEARNERS - Patnaik, Jayashree (PEOPLE: International Journal of Social Sciences, 2020)
A plethora of innovative pedagogical tools got invented of late enriching the episteme of English language teaching, while making the acquisition easy and comfortable for the English language learners. In the present research paper, it is studied how discourse analysis of English fictional texts can be used as a useful pedagogical tool to improve the communicative competence of English language learners. Regular practice of doing the analysis of different discourses from the texts helps the readers/learners to develop the speaking skills in English, through the acquisition of grammatical and semantic knowledge with enhanced vocabulary and specifically with socio-cultural contexts. The analyst has to move from the semantic study of the constituents of narratives, talk exchanges, structures of speech to the linguistic, cognitive, historical, social, rhetorical, psychological reasons for the distinctive forms and functions of discourse in context. Some of the textual extracts are taken here from the selected texts such as pieces of narrative and conversational discourses; and the major objective here is to prove how the different bases and modes of discourse analysis applied help the English language learner to achieve the communicative goal easily.